2021
DOI: 10.3389/fphar.2021.636752
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Potential of Banha-Sasim-Tang for Stress-Sensitive Functional Dyspepsia via Modulation of Ghrelin: A Randomized Controlled Trial

Abstract: Background: Functional dyspepsia (FD) is a highly complex pathophysiologic disease, which shows low recovery and high relapse rates. Therefore, a growing number of clinicians and patients are looking for alternative herbal medicine. Banha-Sasim-Tang (BST) is an herbal prescription for treating a wide range of dyspepsia in traditional Korean medicine (TKM).Aim of the study: This study aimed to evaluate the efficacy of BST on FD in patients with psychological stress-related symptoms and to investigate the involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Two RCTs (Park et al, 2013;Kim et al, 2021) with published study protocols had a low RoB. The remaining 55 studies were biased due to insufficient information.…”
Section: Bias In Selection Of the Reported Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two RCTs (Park et al, 2013;Kim et al, 2021) with published study protocols had a low RoB. The remaining 55 studies were biased due to insufficient information.…”
Section: Bias In Selection Of the Reported Resultsmentioning
confidence: 99%
“…These randomization studies did not report the sequence of allocation concealment. Two studies (Park et al, 2013;Kim et al, 2021) used a center-controlled method to randomize participants and were assessed to have a low RoB.…”
Section: Bias Arising From the Randomization Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Many patients with FD have chosen herbal products from traditional Korean medicine (TKM) and traditional Chinese medicine (TCM). Many studies have shown the therapeutic effects of multiherbal decoctions in clinical trials ( Kim et al, 2014 ; Kim et al, 2021 ) and animal experiments ( Jeon et al, 2019 ; Tan et al, 2020 ). In particular, the pharmacological theories of TKM and TCM emphasize the synergistic actions of multiherbal combinations for the treatment of multifactorial disorders, such as FD ( Liu et al, 2013 ; Kim et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%